DNA methyltransferases hitchhiking on chromatin (Swiss Medical Weekly, 2020)
DNA methylation is an epigenetic modification that plays a central regulatory role in various biological processes. Methyl groups are coupled to cytosines by the family of DNA methyltransferases (DNMTs), where DNMT1 is the main maintenance enzyme and the DNMT3 branch of the family is mostly responsible for de novo methylation. The regulation and function of DNA methylation are dependent on the genomic and chromatin context, such as binding sites for transcription factors or the presence of histone marks. Yet how local context, especially chromatin marks, influences the recruitment of the different DNMTs to their genomic target sites remains to be completely revealed. Elucidating the crosstalk between different histone modifications and DNA methylation, and their combined effect on the genome-wide epigenetic landscape, is of particular interest. Aberrant distribution of chromatin marks that guide DNMT activity or DNMT mutations that influence their correct recruitment to the genome have a profound impact on the deposition of DNA methylation, with consequences for genome function and gene activity. In this review, we describe the current state of knowledge on this topic and provide an overview on how chromatin marks can guide DNMT recruitment in healthy and diseased cells.